The Crocidura fuliginosa species complex (Mammalia: Insectivora) in peninsular Malaysia: Biological, karyological and genetical evidence - Ruedi, M.; Maddalena, T.; Yong, Hoi Sen; Vogel, P. (Elsevier, 1990)
Four West Malaysian shrew populations of the genus Crocidura were investigated through their karyotype and allozyme variations, and, in part, by interfertility experiments. Two different karyotypes characterize these shrews. The first, restricted to the Cameron Highlands (Peninsular Malaysia), invariably has 2n=40 chromosomes but a varying fundamental number (FN-54–58). The second karyotype shows a fundamental number of 62–68 and a polymorphic chromosomal number of 2n=38, 39 or 40, a rare event in the genus Crocidura. Thus both can be distinguished by either a low or a higher number of meta- and submetacentric elements. In heterospecific breeding experiments, mutual avoidance was observed suggesting prezygotic barriers, whereas intraspecific pairs produced 13 litters (mean 2.1 young). Furthermore, our biochemical results indicate that both karyotypes correspond to a relatively ancient separation (Nei's D=0.354), an amount of genetic differentiation comparable to the distance separating them from the West Palearctic C. russula (D=0.429–0.583). In contrast, conspecific island and mainland Malaysian shrews possessing the second karyotype had only one fixed allelic difference over the 35 Loci surveyed. The problem of naming the two biological species remains unsolved and requires further comparative investigations